Educate for Peace and in Peace: Elements to be Considered at School - Montserrat Alguacil; Maria Carme Boqué; María Dolors Ribalta Alcalde (Universidad Autónoma de Madrid, 2019)
Peace education challenges the entire society and overflows the pedagogical debate; thus, the objective of this research is to know the vision of key informants on how the culture of peace can be significantly implemented in the school and contribute to the educational and social improvement. For this reason a sample of representatives from different relevant social fields were selected with the double objective of, on the one hand, taking the debate on peace education in the school to the citizens and, on the other hand, to favor a shared approach of this subject by society at large. To carry on the study, the perception that 25 key informants have about both the importance of peace in education and how to implement it in the school context has been qualitatively analyzed. The results of the study have been interpreted according to Miles and Huberman (1984, 1994) organizing the information to its meaning and establishing metacategories and categories of analysis. The conclusions highlight the need to specify positive peace education in educational regulations, the importance of identifying the competences for peace already present in the curriculum and the creation of training spaces for teachers.